O wykorzystaniu wiadomości sms w nauczaniu komunikacji w języku obcym na przykładzie języka niemieckiego jako języka obcego - Bawej, Izabela (Neofilolog, 2024)
Acquiring proficiency in conveying information through short text messages is clearly connected with the changes that have taken places in the world around us. It should, therefore, find its reflection in the teaching of foreign languages, especially in language studies. It is worth noting that SMS messages, as a means of communication, can be an interesting and useful topic for students who can no longer (or perhaps do not want to) function without a smartphone. The considerations presented here are rooted in educational practice and provide a description of a project aimed at developing proficiency in understanding and creating text messages in practical German language classes. Features included writing with correct spelling, the style of SMS messages, the choice of linguistic elements and the use of abbreviations, both in German and English. The paper also includes examples of exercises and discusses the impact of SMS messages on the progress and quality of German language classes. The project presented aims to demonstrate the relevance of introducing such texts and their didactic value in foreign language teaching. It offers sample solutions that can be employed in the process of developing writing skills in a foreign language and suggests how SMS messages can be used as a communication tool in foreign language classes to broaden and reinforce vocabulary related to mobile phones.